Political and Socio-Economic Dynamics on the Access to Oral Sources at National Archives in Zimbabwe and South Africa. Issue 2 (June 2022) - Bhebhe, Sindiso; Ngoepe, Mpho
Access is one of the fundamental purposes of archives as archives are preserved for use by the public. One can argue that archives that are not being consulted by the researchers may simply be referred to as "dead" or "irrelevant." It is from this assumption that a comparative case study between National Archives of Zimbabwe (NAZ), National Archives and Record Services of South Africa (NARS), and provincial archives in South Africa' oral history units was carried out. The major objectives being that of how accessible are the oral history holdings of NAZ and NARS to the public vis-à-vis the traditional archives such as manuscripts among others and the impact of coloniality to access. Data was collected through interviews and observations including also document analysis. The discussion on collected data revealed a massive underutilization of oral sources which is not in tandem with the spirited effort put by both NAZ and NARS in collecting the oral histories of the once marginalized groups of people. Some of the recommendations offered were the adoption of ICTs especially online archiving and social media in providing access to oral history holdings to the public including coming up with access policies which are in line with the International Council of Archives' (ICA) (2012) Principles of Access.